2013
DOI: 10.1111/fwb.12074
|View full text |Cite
|
Sign up to set email alerts
|

Thermal adaptation affects interactions between a range‐expanding and a native odonate species

Abstract: Summary 1. Increasing temperature and invading species may interact in their effects on communities. In this study, we investigated how rising temperatures alter larval interactions between a naturally range‐expanding dragonfly, Crocothemis erythraea, and a native northern European species, Leucorrhinia dubia. Initial studies revealed that C. erythraea grow up to 3.5 times faster than L. dubia at temperatures above 16 °C. As a result, we hypothesised that divergent temperature responses would lead to rapid siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…For example, aside from the Bass Strait, there are several gaps along the Great Dividing Range that suggest odonate species diverged according to breaks in the terrain (Watson & Theischinger, ). Even if species can disperse to climatically suitable regions, it may not ensure successful establishment (Angert et al ., ), resident species could competitively exclude new arrivals or alternatively, climate change may provide immigrant species with a competitive advantage, displacing resident species (Suhling & Suhling, ). However, research in Victoria has shown the relationship between local and regional richness of macroinvertebrates appears to be linear, suggesting communities are not necessarily saturated, and could accept immigrant species (Marchant et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, aside from the Bass Strait, there are several gaps along the Great Dividing Range that suggest odonate species diverged according to breaks in the terrain (Watson & Theischinger, ). Even if species can disperse to climatically suitable regions, it may not ensure successful establishment (Angert et al ., ), resident species could competitively exclude new arrivals or alternatively, climate change may provide immigrant species with a competitive advantage, displacing resident species (Suhling & Suhling, ). However, research in Victoria has shown the relationship between local and regional richness of macroinvertebrates appears to be linear, suggesting communities are not necessarily saturated, and could accept immigrant species (Marchant et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In other invertebrates, warming to temperatures below the ULL have been associated with increased mortality (Folt et al ., ; Flenner et al ., ; Shama et al ., ; Pelini et al ., ), and temperature can exacerbate the effects of other stressors (Folt et al ., ; Schisler et al ., ; Verberk & Calosi, ) and decrease immune responses even when enhancing other aspects of performance (Karl et al ., ). The presence of an intra‐guild predator can increase mortality with warming in some but not all species of odonates (Suhling & Suhling, ). For species that diapause in the larval stage, warming may prevent them from entering this diapause stage and may elevate metabolic costs and increase mortality (Hassall & Thompson, ).…”
Section: Discussionmentioning
confidence: 99%
“…). However, within odonates, species responses to environmental change can be highly variable and depend on both the context of the warming and the presence of additional stressors (e.g., competitors, potential intraguild predators, food limitation), and on the specific responses quantified (e.g., growth rate, mortality, size at or timing of emergence; Suhling and Suhling , Nilsson‐Örtman et al. , Suhling et al.…”
Section: Introductionmentioning
confidence: 99%